Isolation-Hypoxia and Re-Oxygenation of the Pallial Cavity of Female Crepipatella Dilatata During Estuarine Salinity Changes Requires Increased Glyoxylase Activity and Antioxidant Metabolism to Avoid Oxidative Damage to Female Tissues and Developing Embryos - (:unkn) unknown (ELSEVIER SCI LTD, 2016)
The estuarine slipper limpet Crepipatella dilatata is a gastropod that can survive prolonged periods of low salinities (< 24 PSU) caused by tidal changes and/or prolonged periods of rain. During low salinity events, C dilatata can isolate its body from the outside environment, by sealing its shell against the substrate on which it grows. Prolonged isolation periods from the surrounding environment can greatly lower available oxygen levels inside of the pallial cavity, impacting on the physiology of both females and their incubated encapsulated embryos. When salinity levels return to normal, isolation is terminated and the inflow of seawater results in re-oxygenation. In this study we show that when re-oxygenation of the pallial cavity takes place, oxidative damage, in the form of increased levels of lipid peroxides and protein carbonyls, occurs in both maternal tissues and in incubated embryos. To avoid terminal oxidative damage both females and their embryos increase their levels of the glyoxalase pathway enzymes (GLX-I and GLX-II) and general antioxidant metabolism (SOD, CAT, GR, GPDX and GST). As a result the levels of oxidative damage decline to basal levels within 24 h of reoxygenation. Thus the combination of isolation, a behavioural strategy, combined with encapsulation of embryos and a capacity to up regulate relatively rapidly the glyoxylase pathway and general antioxidant metabolism, play major roles in facilitating the survival of C dilatata in the small estuaries of Southern Chile. (C) 2016 Published by Elsevier Ltd.